EFEKTIVITAS PROGRAM KESEHATAN REPRODUKSI MELALUI CERAMAH OLEH GURU TERHADAP PENINGKATAN PENGETAHUAN TENTANG KESEHATAN REPRODUKSI DAN SIKAP PERMISIF TERHADAP SEKS PRANIKAH PADA SISWA SMP - , PRAMESTI TYAS WIBAWANTI; , Dr. Ira Paramastri, M.Si., Psi. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Permissiveness towards premarital sexual behavior in adolescents may be caused by the lack of information sources about reproductive health that they need. This study aims to increase knowledge about reproductive health and decrease the permissive attitudes toward premarital sexual behavior in junior high school students through a reproductive health program by teachers used lecture methods. The design of experiments in this study using untreated control group design with pretest and posttest. Collecting data used Knowledge Test on Reproductive Health and Permissive Attitude Scale toward sexual behavior. Analysis of the data used mixed Anava technique. The analysis result showed that the reproductive health program was effective to increase knowledge about reproductive health and decrease permissive attitude towards premarital sex in the experimental groups significantly, with F = 98.253 (p <0.05) for knowledge about reproductive health, and F = 30.474 (p <0.05) for permissive attitudes toward premarital sex. Based on these results, it can be concluded that the reproductive health knowledge and refusal toward sexual behavior in the experimental groups was higher than that n the control group.